SLC6A14, a Na(+)/Cl(−)-coupled amino acid transporter, functions as a tumor promoter in colon and is a target for Wnt signaling - Sikder, Mohd O. F. (Biochem J, 2020)
SLC6A14 is a Na(+)/Cl(−)-coupled transporter for neutral and cationic amino acids. It is expressed at basal levels in the normal colon but is up-regulated in colon cancer. However, the relevance of this up-regulation to cancer progression and the mechanisms involved in the up-regulation remain unknown. Here, we show that SLC6A14 is essential for colon cancer and that its up-regulation involves, at least partly, Wnt signaling. The up-regulation of the transporter is evident in most human colon cancer cell lines and also in a majority of patient-derived xenografts. These findings are supported by publicly available TCGA (The Cancer Genome Atlas) database. Treatment of colon cancer cells with α-methyltryptophan (α-MT), a blocker of SLC6A14, induces amino acid deprivation, decreases mTOR activity, increases autophagy, promotes apoptosis, and suppresses cell proliferation and invasion. In xenograft and syngeneic mouse tumor models, silencing of SLC6A14 by shRNA or blocking its function by α-MT reduces tumor growth. Similarly, the deletion of Slc6a14 in mice protects against colon cancer in two different experimental models (inflammation-associated colon cancer and genetically driven colon cancer). In colon cancer cells, expression of the transporter is reduced by Wnt antagonist or by silencing of β-catenin whereas Wnt agonist or overexpression of β-catenin shows the opposite effect. Finally, SLC6A14 as a target for β-catenin is confirmed by chromatin immunoprecipitation. These studies demonstrate that SLC6A14 plays a critical role in the promotion of colon cancer and that its up-regulation in cancer involves Wnt signaling. These findings identify SLC6A14 as a promising drug target for the treatment of colon cancer.